Peran BPPD Provinsi Kepri Dalam Membantu Meningkatkan Kesejahteraan Masyarakat Perbatasan Di Kepulauan Riau Tahun 2024 - Rizky Octa Putri Charin; Aditya Wahyu Saputra; Indra Bastian Tahir (Jurnal Archipelago, 2025)
BPPD of Riau Islands Province is a Regional Apparatus Organization under the auspices of the National Border Management Agency (BNPP). The purpose of this study is to determine the role of BPPD Kepri in helping to improve the welfare of the border communities of Riau Islands Province. The method used in this writing is to use literature study techniques, namely collecting several sources such as books, magazines, journals, and news. The results found in this study are that BPPD of Riau Islands Province plays a role in coordinating and supervising development and utilization in border areas. There are several regencies/cities that are the priority of BPPD of Riau Islands Province, namely Bintan Regency, Batam City, Karimun Regency, Anambas Islands Regency, and Natuna Regency. BPPD Kepri also plays a role in the Malindo Sosek Cooperation in the fields of Health, Industry and Trade, Tourism, Transportation, Safety and Management, and Immigration and Customs.